Pengaruh Kepemimpinan Visioner Kepala Madrasah terhadap Kedisiplinan Guru di MAN 2 Samarinda - Marantika Marantika; Dwi Nur Aini Dahlan (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2019)
Visionary leadership is a capability to make changes by having new visions and ideas, thinking ahead, carrying out stages of mutual interconnection that can influence and motivate teachers and their students. This research aims to find out the effect of leadership of Madrasah Principal Visionary to Teacher Discipline. The type of this research is quantitative research. The population in this study were all 60 teachers in MAN 2 Samarinda. The data of this research is obtained from questionnaire, observation and documentation. The data analysis technique uses product moment correlation formula, determinant coefficient (R²) and t test. The results of this study shows the results of the t-test value of 3.5090> t table 2.00172, which means that Ho is rejected and Ha is accepted. The meaning is there is a correlation between variable X and Y, product correlation 0.416. That means there is a strong correlation between visionary leadership variable and teacher discipline variable. Percentage of visionary leadership for teacher discipline is 17.30% (strong enough), the factors that cause these results include: giving the best performance without analyzing / following new era, inability to change teachers knowledge into strategy, and treating teachers differently causing conflicting duties. The supporting and inhibiting factors in managing teacher discipline include: teacher personalitty, the headmaster teachers supervision.